Conceptual architecture design and configuration of thin client system for schools in Malaysia: a pilot project - Ahlan, Abdul Rahman; Mahmud, Murni; Arshad, Yusri (Institute of Electrical and Electronics Engineers Inc. (IEEE), 2010)
Thin client systems have advanced recently with new innovative design extensions such as virtualisation and cloud computing. Client-server architecture is the basis for thin client system to connect remote multi-workstations to administrative servers located in headquarters or data center. This paper first presents a literature review on thin client concept and virtualization. In the next section, we describe the Wyse Technology and Linux thin client for windows-based and open source solution respectively. We then proceed with description of proposed conceptual architecture design and implementation for primary and secondary schools in Malaysia taking into account International Telecommunication Union and other International standards or benchmarks for high quality of service (QoS) delivery. Finally, our recommendation is that each system design and implementation is unique and thus requires different sets of decision-making criteria before designing an architecture. Networked-schools across a country like Malaysia with heavy users requirements pose high specification in architecture and system design planning to IT divisions. Keywords- Thin clients, virtualization, schools, Malaysia, quality of service